Auto-avaliação dos Discentes do Curso de Ciências Biológicas da Unemat, Campus de Nova Xavantina: um modelo para avaliação das disciplinas curriculares, segundo a percepção do corpo discente e docente - De Sousa Miranda, Érica; Da Silva, Joaquim Manoel [UNESP] (My University, 2011)
This paper presents an evaluation of the curriculum subjects of the Biological Sciences course in the University of the State of Mato Grosso (UNEMAT), Nova Xavantina campus, Brazil. The research was carried out by means of a self-assessment instrument, aimed at searching learners' and educators' points of view. The questionnaires were given in the first, third and seventh semesters, in which students were asked to assess pedagogical aspects regarding professors and their didacticism, as well as the subject matters being taught; in addition, they were invited to evaluate themselves as learners. The data was analyzed using statistical parameters, in order to measure teaching performance, and, subsequently, professors were given the opportunity to express their concepts about the students' assessment. The average value of the overall Cronbach's alpha coefficient was 0.923±0.001, a significant value considering that alpha varies between 0 and 1, which proves the questionnaire to be reliable. The hierarchical cluster analysis (HCA) does not permit teaching performance to be associated with professors' qualification or workload.
Auto evaluation of the students of the Biological Sciences course in the University of the State of Mato Grosso (UNEMAT), Nova Xavantina campus: A model for the evaluation of the curriculum subjects, according to the perception of the faculty and student body
Keywords: Curriculum subjects; Educators; Higher education; Self-assessment; Students